Photophysics of Silicon Phthalocyanines in Aqueous Media. Issue 2 (10th January 2013) - Doane, Tennyson L.; Chuang, Chi‐Hung; Chomas, Andrew; Burda, Clemens
Abstract Phthalocyanines have been used as photodynamic therapy (PDT) agents because of their uniquely favorable optical properties and high photostability. They have been shown to be highly successful for the treatment of cancer through efficient singlet‐oxygen (1O2) production. However, due to their hydrophobic properties, the considerations of solubility and cellular location have made understanding their photophysics in vitro and in vivo difficult. Indeed, many quantitative assessments of PDT reagents are undertaken in purely organic solvents, presenting challenges for interpreting observations during practical application in vivo. With steady‐state and time‐resolved laser spectroscopy, we show that for axial ligated silicon phthalocyanines in aqueous media, both the water:lipophile ratio and the pH have drastic effects on their photophysics, and ultimately dictate their functionality as PDT drugs. We suggest that considering the presented photophysics for PDT drugs in aqueous solutions leads to guidelines for a next generation of even more potent PDT agents.